Increased captures of the critically endangered leatherback turtle (Dermochelys coriacea) around New Zealand: the contribution of warming seas and fisher behavior - Dunn, Matthew R.; Finucci, Brittany; Pinkerton, Matthew H.; Sutton, Philip; Duffy, Clinton A.J. (Frontiers in Marine Science, 2023)
Five species of sea turtles are known to occur in New Zealand waters, with the leatherback turtle (Dermochelys coriacea) being the most frequently reported. In New Zealand all sea turtles are protected, but there are currently no fisheries bycatch mitigation measures. We describe fishery captures of leatherbacks from Ministry observer and fisher self-reported data. A generalized additive model (GAM) was then used to evaluate which factors might explain the observed year trend in captures. Between fishing years 2007–08 and 2020–21 (years starting 1 October), there were 217 captures of leatherback turtles, an annual average of 15.5. Reported captures increased substantially to 50 in 2020–21. Nearly all (97.7%) captures were reported from surface longline fisheries. Because of sparse observer coverage most captures (85.3%) were self-reported by fishers. Within the main fishery, just 9.4% of the vessels reported 94.5% of the leatherback captures, and one vessel reported 40.4% of all captures. Some non-reporting of captures seems likely. The GAM estimated a higher probability of capture with increasing SST from a constant-over-time spatial pattern of monthly sea surface temperature, and predicted the increase in captures in 2020–21. Much of the increase in bycatch could therefore be explained by the fleet moving into warmer areas where the probability of leatherback capture was higher. Capture mitigation measures could include restricting fishing in turtle ‘hotspot’ times and areas. New Zealand waters should be recognized as an important seasonal foraging ground for leatherback turtles where capture mitigation measures are necessary.